Effects of sediment amended with Deepwater Horizon incident slick oil on the infaunal amphipod Leptocheirus plumulosus. Issue 1 (15th August 2016) - Lotufo, Guilherme R.; Farrar, J. Daniel; Biedenbach, James M.; Laird, Jennifer G.; Krasnec, Michelle O.; Lay, Claire; Morris, Jeffrey M.; Gielazyn, Michel L.
Abstract: Crude oil released from the Deepwater Horizon disaster into the Gulf of Mexico posed potential impacts to infaunal invertebrates inhabiting near shore habitats. The effects of sediment-associated weathered slick oil on the amphipod Leptocheirus plumulosus was assessed using 28-d exposures to total PAH sediment concentrations ranging from 0.3 to 24 mg/kg (sum of 50 PAHs or tPAH50). Survival and growth rate were significantly decreased in the 2.6, 11.4 and 24.2 mg/kg treatments, but only growth in 5.5 mg/kg. Offspring production was dramatically decreased but was variable and significantly different only for 24.2 mg/kg. The concentrations associated with 20% decreases relative to reference were 1.05 (95% CI = 0–2.89) mg/kg tPAH50 for growth rate and 0.632 (95% CI = 0.11–2.15) mg/kg tPAH50 for offspring production. The concentrations of PAHs affecting amphipods are within the range of concentrations measured in marsh areas reportedly impacted by DWH oil after its release. Highlights: Amphipods exposed to sediment mixed with oil from the Deepwater Horizon (DWH) spill. 28-d exposures assessed effects on survival, growth and reproduction. Growth was significantly reduced at 2.6 mg/kg total PAHs and higher concentrations. The concentrations associated with a 20% decrease in reproduction was 0.632 mg/kg total PAHs.